Government Liability to Damages Due to Defective Provision of Health Services in Turkey - Guloglu, Yavuz; Yargıcı, Recep (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
Health service is one of the essential public services offered by the Administration with a very comprehensive and expansive staff, and due to the comprehensive nature of the service provided and the fact that the beneficiaries of the service constitute almost every segment of society, many different appearances of defect that may include the compensation responsibility of the Administration may arise. Therefore, the study is mainly about the service defect and the compensation responsibility of the Administration in providing health services within the scope of the responsibility of the Administration based on service defect. In the study, the concept of the responsibility of the Administration and the concepts of defect liability and strict liability, which are the types of responsibility of the Administration, will be discussed first. All will examine the conditions of the responsibility of the Administration. Then, the concept of service defects and the different appearances of service defects, such as poor service, late service, non-operational service, and severe service defect, will be examined. Finally, the service defects specific to health services, which constitute the main framework of the study, will be discussed in light of the decisions of the Council of State on this issue.